CONSEQUENCES OF LAND REFORM IN UKRAINE ON THE EXAMPLE OF GEORGIA AND MOLDOVA - Selezniov , V. I.; Yakubovskiy , S. O. (The actual problems of regional economy development, 2021)
The article is aimed at investigating the expediency of land reform in Ukraine. The process and consequences of land reforms in Georgia and Moldova are considered. The indicators of development of the agricultural sector and the degree of involvement of the population in it are revealed. The world experience of land distribution was analysed. The most effective strategy of land reform development by analysing the research in the dependence of efficiency of land plots utilization on the size of households that cultivate them was revealed. The efficiency of agroholdings and family farms is compared. Determined trends in the distribution and size of plots in developed countries. Analysed the gradual adoption of decisions in the development of land reform and their effects on the success of such reform in Georgia and Moldova. The current decisions of the Ukrainian government on the way to reforming land distribution and use of land resources are considered. Parallels of the current Ukrainian land reform based on the experience of Moldova and Georgia are identified. The assumption of success and expediency of the decisions taken, which could potentially come into force when the Verkhovna Rada of Ukraine discusses the format of the land reform, was put forward. Analysed the further development of the land sector according to the gradual entry into force of the adopted legislation. The issues of expediency of opening the land market to foreigners were considered. Penetrated the experience of international partners and countries already decided on the admission or non-admission of foreign contractors to the national land market. The degree of development of accounting and inventory of existing land plots and completeness of filling the land cadastre of the three countries under study was determined. The research method was the analysis of the current land system of Georgia and Moldova by studying articles on the dynamics of changes in local legislation. The main economic indicators that may indicate the degree of success of the reforms in these countries are considered. Due to such indicators, a detailed analysis of the latest changes in the legislation of Ukraine predicted and assessed the feasibility of the reforms.